The Hotel Study—Clinical and Health Service Effectiveness in a Cohort of Homeless or Marginally Housed Persons. (July 2017) - Honer, William G.; Cervantes-Larios, Alejandro; Jones, Andrea A.; Vila-Rodriguez, Fidel; Montaner, Julio S.; Tran, Howard; Nham, Jimmy; Panenka, William J.; Lang, Donna J.; Thornton, Allen E.; Vertinsky, Talia; Barr, Alasdair M.; et al.
Objective: The Hotel Study was initiated in Vancouver's Downtown East Side (DTES) neighborhood to investigate multimorbidity in homeless or marginally housed people. We evaluated the clinical effectiveness of existing, illness-specific treatment strategies and assessed the effectiveness of health care delivery for multimorbid illnesses. Method: For context, we mapped the housing locations of patients presenting for 552, 062 visits to the catchment hospital emergency department (2005-2013). Aggregate data on 22, 519 apprehensions of mentally ill people were provided by the Vancouver Police Department (2009-2015). The primary strategy was a longitudinal cohort study of 375 people living in the DTES (2008-2015). We analysed mortality and evaluated the clinical and health service delivery effectiveness for infection with human immunodeficiency virus or hepatitis C virus, opioid dependence, and psychosis. Results: Mapping confirmed the association between poverty and greater number of emergency visits related to substance use and mental illness. The annual change in police apprehensions did not differ between the DTES and other policing districts. During 1581 person-years of cohort observation, the standardized mortality ratio was 8.43 (95% confidence interval, 6.19 to 11.50). Physician visits were common (84.3% of participants over 6 months). Clinical treatment effectiveness was highest for HIV/AIDS, intermediate for opioid dependence, and lowest for psychosis. Health service delivery mechanisms provided examples of poor access, poor treatment adherence, and little effect on multimorbid illnesses. Conclusions: Clinical effectiveness was variable, and illness-specific service delivery appeared to have little effect on multimorbidity. New models of care may need to be implemented.